2020
DOI: 10.1016/j.ijcha.2020.100656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sacubitril valsartan on clinical and echocardiographic parameters of outpatients with heart failure and reduced ejection fraction

Abstract: Highlights How sacubitril-valsartan (SV) can affect cardiac remodelling is still unclear. SV therapy is associated with reduction of left ventricular mass and thickness. In our study women had less reverse cardiac remodelling than men. SV therapy also induced a decreased need for loop diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…Even if the magnitude of ARNI-related reverse remodelling described in previous studies is inferior to that observed in our case, [15][16][17] , other studies showed more considerable changes of left ventricular volumes and ejection fraction. 12,18,19 Moreover, in the present case the observed changes of left ventricular volumes and ejection fraction improvement were rapid, similarly to other reports describing significant reverse remodelling only after switching from standard therapy to sacubitril/valsartan in patients with cardiotoxicity. 20 In conclusion, in this case report of relapsing HCL and HFrEF, early ARNI treatment was feasible, safe and accompanied by significant LVEF improvement.…”
Section: Discussionsupporting
confidence: 89%
“…Even if the magnitude of ARNI-related reverse remodelling described in previous studies is inferior to that observed in our case, [15][16][17] , other studies showed more considerable changes of left ventricular volumes and ejection fraction. 12,18,19 Moreover, in the present case the observed changes of left ventricular volumes and ejection fraction improvement were rapid, similarly to other reports describing significant reverse remodelling only after switching from standard therapy to sacubitril/valsartan in patients with cardiotoxicity. 20 In conclusion, in this case report of relapsing HCL and HFrEF, early ARNI treatment was feasible, safe and accompanied by significant LVEF improvement.…”
Section: Discussionsupporting
confidence: 89%
“…Growing evidence has emerged of the role of S/V in modifying the clinical course of HFrEF patients, through its modulation of neurohormonal imbalance [2]. The effect of S/V on left chambers' remodelling has been previously demonstrated by traditional 2D TTE [1,[3][4][5][6][7]23] and speckle tracking analysis [5]. On the contrary, there is a paucity of data on the impact of S/V on RV dimensions and function, which are based exclusively on 2D echocardiographic parameters [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the case of previous myocardial infarction, the LV may undergo profound morphological changes with distortion of its 3D shape, which may be unnoticed by 2D echocardiography [27,28]. Although LV reverse remodelling has been described by 2D TTE at mid-and long-term follow-up after S/V initiation in HFrEF patients [1,[3][4][5][6][7]23], only one study conducted subgroup analyses and found no differences in the 2D LVEF improvement between IHD and non-IHD [29]. Such discrepancy from our results may be ascribed to the short followup (3 months) and the low dose of S/V achieved by patients enrolled in the study by Almufleh et al [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although structural cardiac HFpEF parameters such as left atrial (LA) volume and LV mass should be part of clinical echocardiography for patients with suspected or manifest HF, there may be circumstances when a detailed echocardiographic assessment is unavailable, in geriatric wards or in outpatient clinics with restricted access to echocardiography. In such situations, our results demonstrate that simpler criteria may suffice to identify eligible HFpEF patients 24,25 …”
Section: Discussionmentioning
confidence: 95%